Magnetostructural behavior in the non-centrosymmetric compound Nd7Pd3. (12th April 2019) - Mudryk, Y; Ritter, C; Paudyal, D; Provino, A; Dhar, S K; Manfrinetti, P; Fauth, F; Pecharsky, V K
Abstract: A systematic study of the physical properties and microscopic magnetism of Nd7 Pd3 compound, which in the paramagnetic state crystallizes in the non-centrosymmetric hexagonal Th7 Fe3 -type structure ( hP 20– P 63 mc ; with a   =  10.1367(1) Å and c   =  6.3847(1) Å at 300 K), confirms multiple magnetic ordering transitions that occur upon cooling. Antiferromagnetic transition is observed at T N   =  37 K, which is followed by ferromagnetic transformation at T C   =  33 K. The first-order magnetic transition at T C is magnetoelastic: it involves a change of crystal symmetry from P 63 mc to Cmc 21 and leads to anisotropic changes of the unit cell parameters. While the antiferromagnetic structure is symmetry allowed in P 63 mc, the ferromagnetic structure with magnetic moments along the a -direction of the original hexagonal unit cell induces the first order transition to Cmc 21 . Density functional theory calculations confirm the experimentally observed ground state with the a -axis as the easy magnetization direction.